Effects of locally administered rhBMP‐2 and bisphosphonate on bone regeneration in the rat fibula. (7th June 2018) - Kwak, E‐J; Cha, I‐H; Nam, W; Yook, JI; Park, Y‐B; Kim, HJ
Abstract : Objective: To evaluate the ability of xenogenic bone and absorbable collagen sponge to function as an rhBMP‐2 carrier and the osteoinductivity of bisphosphonate by comparison with recombinant human bone morphogenetic protein‐2 (rhBMP‐2). Materials and Methods: Thirty‐two Sprague‐Dawley male rats were divided into four groups. Segmental ostectomy of both fibulae was performed, and the defect area was then treated with Rapiderm Pad (absorbable collagen sponge; COL_BMP) or CollaOss (xenogenic bone; XENO_BMP) with application of rhBMP‐2. Alternatively, both fibulae were grafted with xenogenic bone with different bisphosphonate concentrations (XENO_Low BP, XENO_High BP). After 4 or 8 weeks, animals were sacrificed, and radiographic, histological, histomorphometric, and immunohistochemical analyses were performed. Results: Recombinant human bone morphogenetic protein‐2 promoted bone formation, regardless of the carrier, and exhibited continuity between the graft material and defect area. Moreover, the results showed that higher concentrations of bisphosphonate were associated with greater bone formation than lower concentrations of bisphosphonate. Conclusion: Absorbable collagen sponges with rhBMP‐2 were advantageous in that there was no remaining graft material and that the bone was remodeled to resemble the existing fibula. The local application of bisphosphonate promoted new bone formation, particularly when used at high concentrations. High‐concentration bisphosphonate induced new bone formation comparable to rhBMP‐2 with lesser remaining bone material.